Status Kualitas Air Pesisir Bukit Ameh di Kawasan Ekonomi Khusus Mandeh di Kabupaten Pesisir Selatan - Garno, Yudhi Soetrisno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTThe Bukit Ameh (Mandeh) area of Pesisir Selatan Regency, West Sumatra, has a potentially unique landscape as a tourist attraction. Therefore, this area will be developed into a special economic area for tourism. However, for doing so, there will be various activities performed there that could affect the environmental conditions there. Accordingly, this study was carried out to determine the quality status of the Bukit Ameh coastal waters to anticipate the impact of various special economic areas for tourism development activities in the future. This study's results indicate that the nutrient content of Bukit Ameh waters has exceeded the Quality Standards. The coastal waters of Bukit Ameh, inhabited by 23 species of phytoplankton from 4 classes with abundance ranging from 795,183 to 3,909,750 ind/m3. Phytoplankton community is dominated by Trichodesmium sp. with the highest population of 2,162,994 ind/m3Ã‚Â or 73.2 percent of total abundance. In addition to Trichodesmium sp., on the coast of Bukit Ameh also found Ceratium sp., Dinophysis sp., and Peridinium sp., which can trigger the Harmful Algal Bloom which is poisonous and can kill other organisms that eat it. Comparing dissolved nutrients and abundance of phytoplankton in several coastal does not show a positive correlation, in the sense that the more fertile the waters, the higher the abundance of phytoplankton.Keywords: water quality, coastal, abundance, phytoplanktonABSTRAKKawasan Bukit Ameh (Mandeh) Kabupaten Pesisir Selatan,Ã‚Â Sumatra Barat,Ã‚Â Ã‚Â merupakan salah satu kawasan pariwisata yang memiliki keunikan bentang alam sebagai daya tarik wisata, sehingga kawasan ini akan dikembangkan menjadi Kawasan Ekonomi Khusus (KEK) Pariwisata.Ã‚Â Terkait hal ini, akan ada kegiatan pengembangan ekonomi yang memiliki potensi mempengaruhi kondisi lingkungan di sana. Oleh karena itu, untuk mengantisipasi dampak dari berbagai kegiatan di KEK pariwisata diÃ‚Â masa datang, maka dilaksanakan penelitian yang bertujuan untuk mengetahui status kualitas perairan pesisir Bukit Ameh. Ã‚Â Hasil penelitian ini mengisaratkan bahwa kandungan nutrien Ã‚Â perairan Bukit Ameh telah melampaui Baku Mutu.Ã‚Â Perairan pesisir Bukit Ameh, dihuni oleh 23 jenis fitopankton dari 4 kelas dengan kelimpahan berkisar antara 795.183-3.909.750 ind/m3.Ã‚Â Komunitas fitoplankton didominasi olehÃ‚Â TrichodesmiumÃ‚Â sp. dengan populasi tertinggi 2.162.994 ind/m3Ã‚Â atau 73,2% kelimpahan total. Ã‚Â Selain Trichodesmium sp., di pesisir Bukit Ameh Ã‚Â juga ditemukan juga Ceratium sp., Dinophysis sp.Ã‚Â dan Ã‚Â Peridinium sp. yang dapat memicu terjadinyaÃ‚Â HarmfulÃ‚Â Algal BloomÃ‚Â yang beracun dan dapat membunuh organisme lain yang memangsanya. Pembandingan nutrien terlarut dan kelimpahan fitoplankton di beberapa perairan pesisir tidak menunjukkan adanya korelasi positif,Ã‚Â dalam arti bahwa makin subur peralihan makin tinggi kelimpahan fitoplankton.Kata kunci: kualitas perairan, pesisir, Ã‚Â kelimpahan, fitoplankton